Fuzzy Adaptive PID Algorithm in Temperature Control System of Lead Patenting Furnace - Junmei Huang; Feiyu Huang; Jintao Liang; Jianxin Chen; Pengtao Li (Advances in Civil Engineering)
In order to enhance the accuracy of temperature control of the patenting furnace, a new temperature control system (TCS) based on the fuzzy adaptive (FA)–proportion integral differential (PID) control algorithm is proposed. The system takes temperature error value and error rate as input and automatically adjusts the PID control parameter value according to the signal of the furnace temperatures to realize adaptive adjustment. Based on the parameter of the FA from simulations, the results of online application showed the temperature fluctuation reduced from 14 to 4°C in Zone I, and it decreased from 15 to 5°C in Zone II. Thus, the accuracy control of operational ability of the TCS was improved obviously. Following practical application, the microstructure analysis of the steel wire postpatenting demonstrated the creation of a more consistently distributed sorbite with enhanced properties by leveraging the new FA-PID system.